X-ray Crystal Structures of Ortho Isomers of Chlorophenylbenzoylthiourea and Nitrophenylbenzoylthiourea - M. Yamin, Bohari; M. Yusof, Sukeri; Sahali Mahadi, Ahamad; A. Kadir, Mahaira (Malaysian Journal of Science, 2002)
Both ortho isomers of chlorophenylbenzoylthiourea (I) and nitrophenylthiourea (II) has trans-cis configuration. The carbonyl-thiourea moiety, O1/C7/N1/C8/S1/N1/C9 of molecule (II) essentially planar but is less planar in (I) with C7 and O1 atoms deviated by 0.198(2) and 0284(1) Å respectively. However the dihedral angle between the aryl and the benzoyl planes in (II) is larger, 78.29(9)° compared with 38.67(10)° in (I). Three six-membered rings are formed in each molecule by three intramolecular hydrogen bondings. In the lattice, the molecules in both compounds are arranged as dimers along the two dimensional axes.